2011
DOI: 10.2106/jbjs.j.00369
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neurologic Lesions After Total Shoulder Arthroplasty

Abstract: The occurrence of peripheral neurologic lesions following reverse shoulder arthroplasty is relatively common, but usually transient. Arm lengthening with a reverse shoulder arthroplasty may be responsible for these nerve injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
149
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(163 citation statements)
references
References 10 publications
9
149
3
2
Order By: Relevance
“…The occurrence of neural injury following shoulder arthroplasty is rare but may be slightly increased in reverse TSA [14]. Relative arm lengthening in reverse TSA is thought to be a possible etiology for these injuries.…”
Section: Neural Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of neural injury following shoulder arthroplasty is rare but may be slightly increased in reverse TSA [14]. Relative arm lengthening in reverse TSA is thought to be a possible etiology for these injuries.…”
Section: Neural Pathologymentioning
confidence: 99%
“…Other reported causes include intraoperative factors such as retractor placement and interscalene nerve block, postoperative hematoma, cement extrusion, screw migration, and humeral shaft fracture [14]. Axillary neuropathy is most frequently reported in reverse TSA and is usually transient [14]. Other nerves that may be injured intraoperatively and following shoulder arthroplasty include the suprascapular nerve and the brachial plexus.…”
Section: Neural Pathologymentioning
confidence: 99%
“…3. Neurological complications after RTSA implantation were studied by Lädermann and colleagues [33]. This study focused on the clinical, radiographic, preoperative and post-operative electromyographic evaluation, with measurement of arm lengthening, according to a previously validated protocol.…”
mentioning
confidence: 99%
“…This can be attributed to the stretch placed on the brachial plexus during humeral positioning and traction during glenoid exposure [33]. Ladderman et al found the prevalence of acute postoperative nerve injury to be significantly more frequent in RSA than in anatomic TSA due to arm lengthening in RSA [34]. In the majority of these cases, however, neurapraxia is the cause and with conservative management, symptoms will completely resolve with time.…”
Section: Nerve Injurymentioning
confidence: 99%